Risk management in Malaysian commercial banks - Hui-Nee, Auyong (2014)
The main purpose of this study is to examine the risk management practices used by Malaysian banks. A content analysis was conducted to 9 commercial banks listed in Bursa Malaysia.This study tries to ascertain the transparency and public disclosure and the understanding of the bank’s risk profile. Furthermore, the Malaysian banks have implemented some effective risk strategies and risk management frameworks.In addition, the credit risk exposure methods are still underused by the Malaysian banks.Similarly, collateral and guarantees continue to be the most commonly used risk mitigation methods to provide support to credit facilities in Malaysian banks.The paper discusses and analyses the current practices in risk management of Malaysian banks.It identifies the tools used in managing credit risk, market risk, liquidity risk and operational risk by Malaysian banks.